So you want to be a writer - Tait, Allison, 1969-; Khoo, Valerie, 1970- (Milsons Point, New South Wales : Australian Writers' Centre Publishing, 2019)
"We won't tell you how or what to write. But we can tell you how to be a writer. We'll look at how to decide what kind of writer you want to be. Where to find ideas, and what to do with them. How to get a book written. How to build a writing business. How to transition into a writing career. And more." --Introduction.
Also available in print.
Mode of Access: Available online.
Keywords: Authorship -- Handbooks, manuals, etc; Handbooks and manuals